Socio-Demographic Changes and Transmission of Tangible and Intangible Resources: Ethnographic Glimpses From the Western Italian Alps - Valentina Porcellana; Giulia Fassio; Pier Paolo Viazzo; Roberta Clara Zanini (Revue de Géographie Alpine)
This article looks at the transmission of tangible and intangible resources from an anthropological perspective and presents two case-studies that provide both interesting commonalities and significant contrasts: the Occitan-speaking (and predominantly Waldensian) upper Pellice Valley, in the western Piedmontese Alps, and Macugnaga, a Walser settlement in the north-eastern Piedmontese Alps. Both localities host linguistic minorities and, demographically, have not suffered massive depopulation. Economically they differ since mountain pastoralism continues to be one of the pillars of economy and culture in the upper Pellice Valley, whereas Macugnaga has converted to tourism. We argue that the current focus on intangible heritage should not obscure the role of tangible assets – such as land, buildings and rights to private and collective resources – which are often essential to ensure that traditional craftsmanship is rescued and preserved. It should also not be taken for granted that the fate of intangible cultural heritage, when it possesses adequate potential, is invariably to turn into tangible, economic resources. Ethnographic research shows that this process may be hindered or mitigated as a results of negotiation between opposite views on the commoditization of cultural heritage. It also suggests that the very survival of a tradition may depend on its being “staged” to the benefit of, and shared with, tourists.